Retinoic acid induces hyaluronic acid production through the klotho-mediated EGFR signaling pathway in human epidermal keratinocytes - Choi, Hyangtae; Lee, Yonghee; Lee, Won-seok; Kim, Beom Joon; Lee, Chang Seok (Archives of Biological Sciences, 2022)
Paper description: The relationship between all-trans retinoic acid (RA) and klotho protein in keratinocytes was examined. Klotho small interfering RNA (siRNA)-transfected keratinocytes were used to study the effect of klotho on hyaluronic acid production and the epidermal growth factor receptor (EGFR) activated extracellular-signal regulated kinase (ERK) pathway in RA-treated cells. RA induced klotho expression, which mediated hyaluronic acid production through the EGFR-ERK signaling pathway. RA behaves as an anti-aging reagent that induces hyaluronic acid production via a klotho-dependent pathway. Abstract: All-trans retinoic acid (RA) is an effective anti-aging chemical substance widely used in skin-care products. RA compromises epidermal differentiation and induces keratinocyte proliferation, causing hyaluronic acid production through mechanisms that are not completely understood. Klotho protein causes the differentiation of human epidermal keratinocytes. Klotho gene expression is mediated by epidermal growth factor (EGF), which inhibits cell apoptosis in aging-related diseases. The klotho gene causes human aging syndrome, including short lifespan, skin atrophy, and osteoporosis. We investigated the relationship between RA and klotho in epidermal keratinocytes for the first time. In human epidermal keratinocytes, RA induced klotho gene expression. Treatment with both RA and recombinant klotho induced hyaluronic acid production in human epidermal keratinocytes. However, in klotho small interfering RNA (siRNA)-transfected keratinocytes, RA produced less hyaluronic acid than in the control group, indicating that RA may partially regulate hyaluronic acid production through a klotho-dependent pathway. Knockdown of klotho gene expression inactivated the EGFR-extracellular signal-regulated kinase (ERK) signaling pathway, which is involved in hyaluronic acid production. We concluded that the effect of RA on hyaluronic acid production is partly regulated through the klotho-mediated EGFR signaling pathway in human epidermal keratinocytes.